Fifty Years of Family Planning in the Democratic Republic of the Congo: The Dogged Pursuit of Progress - Bertrand, Jane T (Routledge Studies on Gender and Sexuality in Africa, 2024)
This book chronicles five decades of struggle to introduce family planning into one of the largest, most complex countries in sub-Saharan Africa: the Democratic Republic of the Congo (DRC). Interweaving details of major political, social, and economic events into the history of family planning in DRC (formerly Zaïre), the book analyses the achievements and setbacks of five decades of programmatic work. President Mobutu’s 1972 discourse on Naissances Désirables (desirable births) opened the door to organized family planning programs, which gained considerable momentum in the 1980s despite societal norms favoring large families. Two pillages and armed conflict paralyzed development work during the decade of the 1990s, and family planning was one of multiple public health programs that struggled to regain lost ground in the 2000s. With new donor funding and implementing agencies, the 2010s witnessed rapid programmatic expansion and improved strategies. By 2018, family planning was operating as a well-oiled machine. But progress is fragile. The book ends by tracing the deleterious effects of the colonial period to contemporary programming and individual contraceptive use. It asks hard questions about donor financing. And it details the six conditions needed to accelerate family planning progress in the DRC, in pursuit of providing millions of Congolese women and men with the means of controlling their own fertility. The book will be of interest to development and public health researchers and practitioners, as well as to historians of the Democratic Republic of the Congo.